Game Edukasi dengan Narasi Bercabang tentang Sejarah Puputan Margarana - Raditya Lungguk Satya Putra; Chrystia Aji Putra; Andreas Nugroho Sihananto (Sekawan Institut, 2026)
History education in Indonesia still tends to be one-sided and lacks interactivity, which can di-minish interest in studying history. In this game, players will take on the role of a fictional young Balinese character who fought to defend Indonesia’s independence in Bali. This study aims to cre-ate an educational game with a branching narrative about the history of the Puputan Margarana. The contribution of this research lies in the application of branching narratives to explore the his-torical story of the Puputan Margarana interactively. This game was developed using a branching narrative with a Branch and Bottleneck narrative pattern for the Windows and WebGL platforms. An evaluation was conducted on 21 junior high school student respondents using the GUESS-18 instrument. The game evaluation results showed an average total score of 4.10 on a 5-point scale, with the Stealth dimension receiving the highest score of 4.24 and the Enjoyment dimension re-ceiving the lowest score of 3.90. Validity test results for the additional dimensions showed that all items were valid (r > 0.443; p < 0.05), and reliability tests confirmed that the additional dimen-sions were reliable (alpha > 0.7). The research results indicate that the developed educational game received a positive response from players.